1984
DOI: 10.1159/000242066
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Blood-Brain Barrier Permeability in Neonatal Cytotoxic Brain Edema: Laboratory and Morphological Findings Obtained on Newborn Piglets with Experimental Pneumothorax

Abstract: Acute, bilateral pneumothorax (PT) was produced in 14 newborn piglets. The clinical status of the operated and 14 control animals was monitored by measuring the arterial blood gases, acid-base balance and mean arterial blood pressure. Different brain regions were processed for electron microscopy and albumin immunohistochemistry; water and electrolyte contents were also determined at the end stage of experimental intervention. Electron microscopy showed more intense pinocytotic activity in the endothelium of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The lower degree of damage observed in the pons in the asphyxiated animals might have originated from the better-maintained blood flow and oxygenation of the brain stem structures as compared with those of other brain regions during asphyxia. Moreover, a cerebral intraparenchymal sodium accumulation was demonstrated earlier in our neonatal pneumothorax model both in vitro (18,62) and in vivo (19,63).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The lower degree of damage observed in the pons in the asphyxiated animals might have originated from the better-maintained blood flow and oxygenation of the brain stem structures as compared with those of other brain regions during asphyxia. Moreover, a cerebral intraparenchymal sodium accumulation was demonstrated earlier in our neonatal pneumothorax model both in vitro (18,62) and in vivo (19,63).…”
Section: Discussionsupporting
confidence: 75%
“…The clinical status of the animals worsened continuously, and by the end of 1 h after the induction of pneumothorax, gasping, bradyarrhythmia, arterial hypotension, hypoxemia, and severe combined acidosis had developed. The pneumothorax was then relieved, and the response to therapy was controlled by transillumination (Wild M4000 fiberscope, Heerburgg, Switzerland) of the thorax (18,22,23). Asphyxiated animals were randomly divided into two groups.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison with our hypoxia protocol, combining hypercapnia with severe hypoxia will better simulate clinical asphyxia. Apart from alveolar hypoxia as in the current protocol, other approaches to induce hypoxia include the creation of pneumothorax 14 , halting mechanical ventilation 15 and the addition of carotid artery occlusion for cerebral ischemia. We attempt to make the hypoxia and reoxygenation clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Polyrnorphonuclear neutrophils augment but it are not essential for this early BBB abnormality (3,6). Previous observations suggest that increased NaF permeability is associated with an enhanced vesicular transport in brain capillary endothelium ( 14,18,25). It is also worthwhile to mention that it has been shown that polymyxin B, an endotoxin-neutralizing drug, improved the outcome of the experimentally induced bacterial meningitis (26).…”
Section: Discussionmentioning
confidence: 99%